Rediscovery of Turnera pernambucensis (Passifloraceae s.l.) in the northern Atlantic Forest and an update for its description - Zelenski, Andréia; Rocha, Lamarck; Louzada, Rafael B. (Phytotaxa, 2016)
Turnera pernambucensis is a shrub endemic to the Brazilian Atlantic Forest previously known only from the type specimen collected 179 years ago. An extant population was found in semideciduous seasonal forest in the state of Pernambuco and new morphological and ecological information is presented here. Illustrations, conservation status and comments about its morphological variation are also provided, as well as a discussion about similarities with morphologically related species of the series Capitatae.